Experimental investigation on the optimal formulation of dune sand concrete reinforced with date palm fibers - Rezig, Salima; Bouaziz, Ahmed; Zatar, Abdallah (Journal of Applied Engineering Science & Technology, 2017)
The main objective of this study is to propose an optimal formulation of sand concrete. The experimental approach consists in fixing the cement dosage at 350 kg / m3 and, in the first phase, to investigate the optimum proportions of each constituent (limestone filler, silica fume, water and adjuvant). The second phase of this study was reserved for the effect of date palm fibers on the optimal formulation deduced from the experimental program of the first phase. The date palm fiber mass rates studied are: 0.5%, 1%, 1.5% and 2%. The results obtained from the first phase made it possible to fix the desired optimal composition equivalent to a unit volume of sand concrete (1 m 3 ). The cement dosage was maintained at 350 kg, dune sand, alluvial sand, fine limestone, silica fume, water and superplasticizer were optimized respectively as follows: 423.98 kg; 980.34 kg; 165 kg; 35 kg; 210 kg and 2%.The results obtained from the second phase show different tendencies in compression than in indirect traction. Indeed, a reduction in resistance was recorded in compression as a function of the increase in the rate of the reinforcement of date palm fibers. This progressive decrease can reach 27% when the rate of reinforcement is equal to 2%. On the other hand, a fluctuation in the results of traction in the range of 5 to 6 MPa was recorded. The maximum tensile strength was reached at a date palm fiber content of 1%. The results obtained from the mass loss measurements clearly showed that the increase in the fiber reinforcement rate induces a decrease in the mass loss estimated at 23.5 %.